Perancangan Interior Pusat Pelatihan Batik di Surabaya - Hadi Hutomo; Andereas Pandu Setiawan (Intra, 2014)
Abstrac— Batik is a high-value artwork and has become part of the cultural heritage of Indonesia (especially Java) since long. East Java actually has a typical batik motifs but many people do not understand about the philosophy and process of making the batik. As the capital of Surabaya in East Java and also the second largest city in Indonesia is a good place to built Batik Training Center. Hopefully, through this design can be a forum for lovers of batik in East Java to pour their love of batik while preserving the cultural heritage of Indonesia.